Answer:
P[(X=n+k)] ∩ X>n)] =P[X=K]
Step-by-step explanation:
If X is a geometric random variable then
for success probability = p
so for failure q= 1-p
Now as given
[tex]P_{x}(n)=(1-p)^{x-1}P_{}[/tex]
Now for the P parameter we have
x∈{1,2,3,....∞}
[tex]P [X=K] = (1-P)^{K-1}P_{}[/tex]
[tex]P [X=n+K] = (1-P)^{n+K-1}P_{}[/tex]
[tex]p[\frac{X=n+K}{X>h}]=\frac{[(X=n+K)n,X>n]}{P(X>n)}[/tex]
[tex]P(X>n)=\sum_{i=n+1}^{\infty}(1-P)^{i-1}P^{} \\[/tex]
[tex]P(X>n)=P\sum_{i=n+1}^{\infty}(1-P)^{i-1}^{}[/tex]
[tex]P(X>n)=P\frac{1-P}{1-(1-P)^{n} } =(1-P)^{n}[/tex]
P[(X=n+k)] ∩ X>n)] = P(X=n+K)
P[(X=n+k)] ∩ X>n)] = [tex]\frac{(1-P)^{n+k-1}P }{(1-P)^{n} }[/tex]
P[(X=n+k)] ∩ X>n)] = [tex](1-P)^{k-1} .P[/tex]
P[(X=n+k)] ∩ X>n)] =P[X=K]